Analysis of Students Science Literacy Skills in Full Day Junior High School (Journal of Innovative Science Education, 2018)
Measurement achievement of scientific literacy skills in students is very important to know the extent to which students have literacy science and become an international benchmark for the quality of a country education. The purpose of this study is to describe the achievement of scientific literacy skills of students in full day junior high school Semarang in science subject of solar system material. This research uses mixed method concurrent triangulation. In general, the tests results of science literacy skills achievement of students in junior full day school Semarang in middle category were a percentage score by an average 33.55%, namely science as a body of knowledge by 8.44%, science as a way of investigating by 4.41%, science as a way of thinking by 8.38%, Interaction of science, environment, technology, and society by 12.32%. Based on the results of research and discussion can be concluded that the achievement of scientific literacy skills of students in junior full day junior high school Semarang is middle category and necessary to increase the achievement of science literacy skills in students. System full day school still have not been able to develop the quality of education and prepare students for the challenges of the development of the modern era. Hopefully this research could eventually become the latest reference achievement of science literacy skills of students in the education system full day school and become material evaluate for education so the result could be recommendation about the education system to improve science literacy.